2023
DOI: 10.1002/ece3.10627
|View full text |Cite
|
Sign up to set email alerts
|

Let's stick together: Infection enhances preferences for social grouping in a songbird species

Marissa M. Langager,
James S. Adelman,
Dana M. Hawley

Abstract: Acute infections can alter foraging and movement behaviors relevant to sociality and pathogen spread. However, few studies have directly examined how acute infections caused by directly transmitted pathogens influence host social preferences. While infected hosts often express sickness behaviors (e.g., lethargy) that can reduce social associations with conspecifics, enhanced sociality during infection might be favored in some systems if social grouping improves host survival of infection. Directly assaying soc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 59 publications
0
1
1
Order By: Relevance
“…Mycoplasma infection status was not related to social behavior during feeding or roosting, suggesting that the social interactions of griffon vultures do not impact mycoplasma infection. Our findings contrast with previous studies in which birds that were more social were also more likely to be infected with mycoplasma (Dhondt et al, 2007;Adelman et al, 2013;Adelman et al, 2015;Sawicka et al, 2020;Hawley et al, 2021;Briard & Ezenwa 2021;Langager et al, 2023). Thus, social behaviors may have different implications for mycoplasma spread across different bird and bacteria species (Sumithra et al, 2013;Sawicka et al, 2020).…”
Section: Discussioncontrasting
confidence: 99%
“…Mycoplasma infection status was not related to social behavior during feeding or roosting, suggesting that the social interactions of griffon vultures do not impact mycoplasma infection. Our findings contrast with previous studies in which birds that were more social were also more likely to be infected with mycoplasma (Dhondt et al, 2007;Adelman et al, 2013;Adelman et al, 2015;Sawicka et al, 2020;Hawley et al, 2021;Briard & Ezenwa 2021;Langager et al, 2023). Thus, social behaviors may have different implications for mycoplasma spread across different bird and bacteria species (Sumithra et al, 2013;Sawicka et al, 2020).…”
Section: Discussioncontrasting
confidence: 99%
“…Intriguingly, recent research has revealed that infection with the bacterial pathogen Mycoplasma gallisepticum Edward and Kanarek, 1960 (Mycoplasmatales: Mycoplasmataceae) can lead to an increase in social preferences among juvenile house finches Haemorhous mexicanus (P.L. Statius Muller, 1776) (Passeriformes: Fringillidae) [35]. Specifically, infected finches spent more time associating with healthy flocks compared with uninfected individuals, with significant implications for Mycoplasma transmission.…”
Section: Introductionmentioning
confidence: 99%